INOVASI DAN EFEKTIVITAS PELAYANAN MELALUI MOBILE JKN PADA BPJS KESEHATAN DI JAKARTA SELATAN - Angelita, Meigy; Lukman, Sampara; Tahir, Irwan (Medium: Jurnal Ilmiah Fakultas Ilmu Komunikasi, 2021)
The development of technology-based health services is one of the public service innovation in the context of reforming the bureaucracy of Indonesian government. This study aims to provide an overview and analyze the assessment of the success, and effectiveness of the application of technology-based services through Mobile JKN at BPJS Kesehatan at the South Jakarta Main Branch Office. Researchers used qualitative methods to describe and gain a thorough and in- depth understanding of technology-based public service innovations focused on the use of the JKN mobile application as a form of innovation in national health insurance services at the Health Social Security Administering Body (BPJS). The JKN-KIS Mobile Application can be categorized as an innovation because it has the attributes of relative advantage, compatibility, complexity, triability, and observability. Researchers use the theory of service effectiveness according to David Krech, Richard an Egerton and mention that the innovations implemented by BPJS in this case, especially the Mobile JKN-KIS innovation at the South Jakarta Branch Office, have been effective.